Immobilization of iodine waste via the gas-pressure sintering of glass-bonded iodosodalite ceramic. Issue 11 (1st June 2022) - Feng, Yaxin; Wei, Guilin; Zhang, Zhentao; Liu, Yi
Abstract: The treatment of radioactive iodine waste is significant for the development of the nuclear industry. In this study, gas-pressure sintering was initially used to immobilize simulated iodine waste. The sintered matrix consisted of iodosodalite and amorphous phases, which was verified by morphological analyses. Transmission electron microscopy results revealed the morphology of iodosodalite and the distribution of related elements. Furthermore, the main form of iodine was proven to be iodide through valance-state results, which is consistent with the observation of iodosodalite phase. Based on the product consistency test standard leaching experiment, the concentration of iodine decreased rapidly in the first 14 days and then stabilized on the order of magnitude 10 -4 g m -2 d -1, indicating the considerable leaching resistance of the sintered matrix. This work proposes the disposal of iodine waste by obtaining iodosodalite via gas-pressure sintering technology. Graphical abstract: Image 1